Quantitative metallography in the research of ferrous and non-ferrous alloys - Dionicio Padilla, Eusebio (2001)
The present investigation has determined the average measure of grain size, including a Jeffries planimetric procedure in materials such as SAE 1010 carbon steel, and AISI 316 stainless steel. Likewise, the digital camera incorporated into the metallographic microscope, has enabled the application of image analysis for the study of the microstructure of materials.